2023
DOI: 10.3389/fpubh.2023.1260571
|View full text |Cite
|
Sign up to set email alerts
|

The effect of urban–rural health insurance integration on consumption of middle-aged and older adult households in rural areas: evidence from China

Lianjie Wang,
Qi Hu

Abstract: IntroductionRural consumption is crucial in promoting economic and social development in China’s economic slowdown. Integrating urban-rural residents’ health insurance has alleviated the financial burden of medical expenses for rural households and boosted rural household consumption. This study examines the effect of integrating urban–rural residents’ health insurance on the consumption patterns of middle-aged and older adult households in rural China. Our research provides a reference basis for improving rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Due to the availability of data and the presence of unique variables, we were compelled to utilize cross-sectional data, which can potentially introduce endogeneity problems. Therefore, referring to the methods of the existing literature ( 16 , 56 ), we further employed the propensity score matching (PSM) method and the instrument variable (IV) approach to overcome the potential endogeneity problems in OLS estimations. Besides, we replaced the measurements of consumption and BPHS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the availability of data and the presence of unique variables, we were compelled to utilize cross-sectional data, which can potentially introduce endogeneity problems. Therefore, referring to the methods of the existing literature ( 16 , 56 ), we further employed the propensity score matching (PSM) method and the instrument variable (IV) approach to overcome the potential endogeneity problems in OLS estimations. Besides, we replaced the measurements of consumption and BPHS.…”
Section: Discussionmentioning
confidence: 99%
“…Middle-aged and older adult individuals are more focused on preventive medical services, while the overall resident population tends to prioritize the treatment of acute illnesses. For example, Wang et al investigated the impact of health insurance on economic performance using the middle-aged and older adult population in China as the study subjects, revealing that health insurance alleviates residents' economic burden and enhances consumption capacity ( 42 ). Liu and Zhao taking the entire resident population as the study subjects, found that health insurance did not reduce the economic burden ( 43 ).…”
Section: Research Hypothesis and Frameworkmentioning
confidence: 99%